Penerapan Metode Simple Additive Weighting (SAW) Untuk Penentuan Skala Prioritas Pada Sistem Seleski Calon Penerima Zakat Baznas - Sularno, Sularno; ., Zulfahmi; Anggraini, Putri; Finarsih, Endang Ulfa; Amanda, Wilia Zulkifni (LPPM Universitas Dharma Andalas, 2024)
This research aims to design a decision support system for determining prospective zakat scholarship recipients at BAZNAS West Pasaman Regency using the Web-based Simple Additive Weighting (SAW) method. Another aim is to find out the problems faced by BAZNAS in determining prospective zakat scholarship recipients using the Web-based Simple Additive Weighting (SAW) method. The research was carried out directly in the field using interview techniques, then by studying books and literature related to the problem being discussed. After the data is collected, the data is grouped and analyzed using the Unified Modeling Language (UML). The results of the analysis are applied to a phpmysql-based data processing information system application program. The methodology that guides system development activities is SDLC. The SDLC model used in this research is the WaterFall Model. It is hoped that the results of this research will help make it easier for prospective scholarship recipients to register for the West Pasaman Baznas scholarship, make it easier for admin to manage, determine prospective West Pasaman Baznas scholarship recipients and shorten the time for selecting management and acceptance of West Pasaman Baznas scholarship candidates.